Arts Council director helps plan new group to coordinate efforts (Raton, NM Raton Range, 1993)
Article about Jackie Erwin traveling to Santa Fe for a newly-formed State Presenter's Network and participating in the organization formation.
Newspaper article
Master list item #: 17
File location is in the Raton file Cabinet
Keywords: Erwin, Jackie -- Arts Council General Director; New Mexico Arts Division; New Mexico Dance -- Dance Troupe; Art Programs; Arts and Humanities Council; National Endowment for the Arts; Santa Fe, New Mexico; Raton, New Mexico